Barriers and facilitators for the implementation of health condition and outcome registry systems: a systematic literature review. (11th January 2022) - Lazem, Mina; Sheikhtaheri, Abbas
Abstract: Objective: Health condition and outcome registry systems (registries) are used to collect data related to diseases and other health-related outcomes in specific populations. The implementation of these programs encounters various barriers and facilitators. Therefore, the present review aimed to identify and classify these barriers and facilitators. Materials and Methods: Some databases, including PubMed, Embase, ISI Web of Sciences, Cochrane Library, Scopus, Ovid, ProQuest, and Google Scholar, were searched using related keywords. Thereafter, based on the inclusion and exclusion criteria, the required data were collected using a data extraction form and then analyzed by the content analysis method. The obtained data were analyzed separately for research and review studies, and the developed and developing countries were compared. Results: Forty-five studies were reviewed and 175 unique codes were identified, among which 93 barriers and 82 facilitators were identified. Afterward, these factors were classified into the following 7 categories: barriers/facilitators to management and data management, poor/improved collaborations, technological constraints/appropriateness, barriers/facilitators to legal and regulatory factors, considerations/facilitators related to diseases, and poor/improved patients' participation. Although many of these factors have been more cited in the literature related to the developing countries, they were found to be common in both developed and developing countries. Conclusion: Lack of budget, poor performance of managers, low data quality, and low stakeholders' interest/motivation on one hand, and financing, providing adequate training, ensuring data quality, and appropriate data collection on the other hand were found as the most common barriers or facilitators for the success of the registry implementation.